К вопросу о тестовых задачах для кругового цилиндра - Ткачук, Николай Николаевич (НТУ "ХПИ", 2007)
Jn the paper the construction of a series of master solutions for circular cylinder is discussed. These solutions were applied to verify a finite element model with two cases of boundary loading.
Keywords: конечноэлементное моделирование; механическая система; контакт упругих тел; эталонные решения; верификация моделей конструкций; задача теории упругости